Electrodiagnosis of dichromacy - Barboni, Mirella Telles Salgueiro; Hauzman, Einat; Nagy, Balázs Vince; Martins, Cristiane Maria Gomes; Aher, Avinash; Tsai, Tina I.; Bonci, Daniela Maria Oliveria; Ventura, Dora Fix; Kremers, Jan (Vision research, 2019)
Retinal and cortical signals initiated by a single cone type can be recorded using the spectral compensation (or silent substitution) paradigm. Moreover, responses to instantaneous excitation increments combined with gradual excitation decreases are dominated by the response to the excitation increment. Similarly, the response to a sudden excitation decrement dominates the overall response when combined with a gradual excitation increase. Here ERGs and VEPs were recorded from 34 volunteers [25.9 ± 10.4 years old (mean ± 1 SD); 25 males, 9 females] to sawtooth flicker (4 Hz) stimuli that elicited L- or M-cone responses using triple silent substitution. The mean luminance (284 cd/m 2 ) and the mean chromaticity (x = 0.5686, y = 0.3716; CIE 1931 color space) remained constant and thus the state of adaptation was the same in all conditions. Color discrimination thresholds along protan, deutan, and tritan axes were obtained from all participants. Dichromatic subjects were genetically characterized by molecular analysis of their opsin genes. ERG responses to L-cone stimuli were absent in protanopes whereas ERG responses to M-cone stimuli were strongly reduced in deuteranopes. Dichromats showed generally reduced VEP amplitudes. Responses to cone-specific stimuli obtained with standard electrophysiological methods may give the same classification as that obtained with the Cambridge Colour Test and in some cases with the genetic analysis of the L- and M-opsin genes. Therefore, cone-specific ERGs and VEPs may be reliable methods to detect cone dysfunction. The present data confirm and emphasize the potential use of cone-specific stimulation, combined with standard visual electrodiagnostic protocols.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Color vision; Cone-isolating stimulus; Electroretinogram; Opsin gene; Silent substitution; Spectral compensation; Visual evoked potential